The External Effects of Black Male Incarceration on Black Females - Mechoulan, Stéphane (Journal of Labor Economics, 2011)
This article examines how the increase in the incarceration of black men and the sex ratio imbalance it induces shape the behavior of young black women. Combining data from the Bureau of Justice Statistics and the Current Population Survey to match male incarceration rates with individual observations over two decades, I show that black male incarceration lowers the odds of black nonmarital teenage fertility while increasing young black women’s school attainment and early employment. These results can account for the sharp bridging of the racial gap over the 1990s for a range of socioeconomic outcomes among females.